Penerapan Storytelling sebagai Intervensi untuk Menurunkan Derajat Stres pada Anak Leukemia (Perancangan dan Uji Coba Penerapan Storytelling dengan Pendekatan Positive Psychology untuk Menurunkan Derajat Stres pada Anak Leukemia Usia 8 Tahun yang sedang M - ACHMAD, ANGGIA PUTRI ATIADANY; SIREGAR, JUKE; NOVIANTI, LANGGERSARI ELSARI; TEHUTERU, EDI SETIAWAN (Indonesian Journal of Cancer, 2015)
ABSTRACTThe aim of this study is to obtain intervention techniques through storytelling and its influence on the degree of stres in children with leukemia, aged 8 years (middle and late childhood). The participant in this study is 8 year old leukemia patient who experiences stres on âtend to highâ category, based on the stres degree scale. The measurement tools of stres was designed by researcher based on Sarafino and Smithâs theory of stres (2001) with the alpha coefficient of reliability is 0.893.In this study, purposive sampling be applied to select the participants and had to go through the medical examinationby which an oncologist. Through the medical examination, two of four children have experienced stres on the âtend to highâ category, but only one children was permitted to be participant due to physical condition. Intervention with storytelling techniques was implemented after doctor states the patient not in aplasia condition.Intervention was given over 6-days period for 40-60 minutes each session.Result showed a decrease of stres degree after the intervention. This conclude that storytelling technique can be used to reduce the stres degree of leukemia patient aged 8 years. This indicated that through the storytelling method, the participant were identified themselves with the same characterâs experiences, moreover the children are able to take the values contained in the story to be applied in his life. The story technique allowed them to express the emotions and cultivate positive emotions, so that children are able to recognize their positive strength and develop it as one of themethods to coping the stres.Â ABSTRAKPenelitian ini bertujuan mendapatkan teknik intervensi melalui storytelling dan pengaruhnya terhadap derajat stres pada anak dengan leukemia usia 8 tahun (middle and late childhood). Partisipan penelitian adalah satu (1) orang pasien leukemia berusia 8 tahun yang diketahui mengalami stres pada kategori âcenderung tinggiâ berdasarkan skala derajat stres. Alat ukur derajat stres disusun sendiri oleh peneliti berdasarkan teori stres Sarafino dan Smith (2011). Skala derajat stres memiliki reliabilitas 0,893 melalui pengukuran alpha Cronbach.Penjaringan subjek dilakukan dengan teknik purposive sampling yang melibatkan pemeriksaan medis oleh dokter onkologi anak. Dari 4 pasien leukemia usia 7â11 tahun yang direkomendasikan oleh dokter, ditemukan 2 orang pasien yang memiliki derajat stres berada pada kategori âcenderung tinggiâ. Hingga penelitian ini selesai dilaksanakan, 1 dari 2 orang pasien tersebut mengalami kondisi fisik yang sangat lemah sehingga tidak diijinkan untuk menjadi subjek penelitian. Oleh karena itu, penelitian ini hanya melibatkan 1 orang anak leukemia. Setelah dilakukan pemeriksaan fisik oleh dokter yang menangani pasien dan dinyatakan bahwa secara fisik pasien tidak mengalami kondisi aplasia maka peneliti melakukan intervensi melalui teknik storytelling. Intervensi diberikan selama 6 hari, berturut-turut dalam kurun waktu 40â60 menit per pertemuan.